Ecological Study of Citrus Plants (Citrus SPP.) in The Gunung Leuser National Park Area Southeast Aceh - Muhammad Husaini Assauwab; Deden Sumoharjo; M Indera; Barokah (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Citrus is one of the strategic horticultural commodities with high economic and genetic value, yet its ecological basis in natural habitats remains understudied, particularly in conservation areas. This study aimed to assess the ecological conditions of wild-growing citrus plants (Citrus spp.) in the Gunung Leuser National Park (TNGL). A descriptive exploratory method was employed, combining field surveys with direct observations and quantitative measurements of environmental variables, including air and soil temperature, humidity, light intensity, rainfall, and elevation. The results indicate that citrus plants can grow at air temperatures of 18–31.6 °C, soil temperatures of 22–23 °C, air humidity of 79.4–80.3%, light intensity of 27.6–2871 lux, annual rainfall of 2,500–4,000 mm, and altitudes of 350–400 m above sea level. These conditions reflect a humid tropical ecosystem favorable for wild citrus growth. The findings demonstrate the citrus plant’s adaptability to shaded, moist environments, and its potential as a source of valuable local germplasm. This study provides a scientific basis for the conservation, management, and further development of adaptive citrus varieties suited to tropical forest conditions.